2012
DOI: 10.1111/ejn.12087
|View full text |Cite
|
Sign up to set email alerts
|

Upstairs/downstairs revisited: spatial pretraining‐induced rescue of normal spatial learning during selective blockade of hippocampal N‐methyl‐d‐aspartate receptors

Abstract: Spatial pretraining can enable spatial learning in another environment that ordinarily requires hippocampal N-methyl-d-aspartate (NMDA) receptor activity to become independent of that activity. This study explored further the circumstances in which this training-induced 'rescue' of later learning in the presence of the NMDA receptor antagonist 2-amino-5-phosphonovaleric acid (D-AP5) can occur. D-AP5 (0, 10, 20 and 30 mm in artificial cerebrospinal fluid) was infused continuously (0.5 μL/h, from a minipump) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 47 publications
3
30
0
Order By: Relevance
“…Spatial learning in the second task was still sensitive to hippocampal lesion, showing that circuits through the hippocampus were still required even though NMDA-dependent plasticity was dispensable. This result has been revisited recently with quantitative and anatomically specific NMDA receptor blockade and replicated the basic finding at inhibitor levels sufficient to block dentate gyrus LTP measured in vivo [27]. …”
Section: Finding the Engram Criteria 1 And 2: Cellular Mechanisms Of mentioning
confidence: 64%
See 1 more Smart Citation
“…Spatial learning in the second task was still sensitive to hippocampal lesion, showing that circuits through the hippocampus were still required even though NMDA-dependent plasticity was dispensable. This result has been revisited recently with quantitative and anatomically specific NMDA receptor blockade and replicated the basic finding at inhibitor levels sufficient to block dentate gyrus LTP measured in vivo [27]. …”
Section: Finding the Engram Criteria 1 And 2: Cellular Mechanisms Of mentioning
confidence: 64%
“…Nevertheless, it seems clear that rodents can form spatial memories even in the absence of hippocampal NMDA receptor function. While there are a number of possible interpretations of these results (for example [27]) taken together, it is difficult to argue that NMDA-dependent LTP in the hippocampus meets the criterion of necessity for a cellular mechanism of spatial learning.…”
Section: Finding the Engram Criteria 1 And 2: Cellular Mechanisms Of mentioning
confidence: 99%
“…in the absence of any drug), and were then tested in the presence of D-AP5 (30 mM) in a completely novel spatial environment (i.e. a completely different laboratory), then the NMDAR antagonist was now found to have little, if any, effect on acquisition of the open-field, spatial reference memory task (the spatial upstairs/downstairs task [15]; see also [16,17]). Therefore, these pharmacological studies also demonstrated that hippocampal NMDARs are not required for (i) spatial navigation per se , (ii) forming a cognitive map of a novel environment, nor (iii) forming a long-term association between a particular spatial location and an outcome (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The second issue is that drug diffusion through a brain area is often incomplete such that sub-areas of a given circuit which are less affected by the drug may be used for second learning that are not used for the first [66]. If pharmacological studies have the advantage of 'reversibility', they have the major difficulty that it is extremely difficult to maintain drug concentrations at a steady-state over time or to ensure effective distribution of a drug within a brain area or network without affecting another ostensibly independent region [67].…”
Section: (B) Anterograde Alterationsmentioning
confidence: 99%